Effects of Nanohydroxyapatite and Fluoride varnish on the Microhardness of the Artificially Induced Enamel Lesion: An In-Vitro Study (Mustansiria Dental Journal, 2025)
Study objective: To evaluate the ability of nanohydroxyapatite and fluoride varnish to remineralize an artificially induced enamel lesions. Methods: Fifty-four extracted premolar teeth were randomly allocated into three main groups (n=18) that are nanohydroxyapatite (n‑HA), fluoride varnish (FL) and untreated groups (C). The groups were further classified into three subgroups (n=6) based on the storage time in artificial saliva (1 week, 2 weeks, 4 weeks). All teeth subjected to pH cycling procedure for induction of white spot lesion. The nHA group was treated by immersing the samples in 10% n-HA solution for three minutes before storing them in artificial saliva. This procedure was repeated daily. Second group treated with fluoride varnish and third group left untreated. Microhardness was measured after 1 week, 2 week, 4 week from first time of application of treatment agents. Results: Statistical analysis of mean microhardness values demonstrated a significant difference in microhardness values according to different storage times only for the nanohydroxyapatite group while there was no significant differences in microhardness mean values for fluoride varnish and untreated group. Conclusion: 10% nanohydroxyapatite suspension more effective in remineralizing of WSLs as compare to fluoride varnish.